Problematika Legal Standing Putusan Mahkamah Konstitusi - Ramdan, Ajie (Jurnal Konstitusi, 2014)
Constitutional Court received a petition for the constitutionality of Law No. 22 of 2001 on Oil and Gas and Law No. 8 of 2011 on the Amendment of the Law No. 24 of 2003 on the Constitutional Court against the Constitution of the Republic of Indonesia Year 1945 Three issues are addressed in this study is about (1) the legal standing of the applicant in the judicial review of Law No. 22 of 2001 on Oil and  Gas and the Law number 8 of 2011 concerning Amendment to Law number 24 Year 2003 concerning the Constitutional Court; (2) consideration of constitutional court give legal standing to the applicant in the judicial review of Law No. 22 of 2001 on Oil and Gas and Law No. 8 of 2011 on the Amendment of Law Number 24 Year 2003 concerning the Constitutional Court; and (3) the proposed granting legal standing of the applicant in the case of judicial review in the Constitutional Court. To answer these problems, this research using material in the form of the decision of the Constitutional Court law, legislation, and writings relating to constitutional law. The type of this research is the juridical-normative. Theory in assessing the applicant has legal standing or not, one of which is the theory of legal standing. Theory of point d’interet legal standing point d’action that is without the benefit of no action. The petitioner in case No. 36/PUU-X/2012 and No. 7/PUU-XI/2013 does not have legal standing to appeal. Court is not appropriate to assess the applicant in case No. 36/PUU-X/2012 and No. 7/PUU-XI/2013 have no legal standing. Because the applicant does not have a base (interest) to apply for judicial review. In addition there are constitutional judges dissenting opinion affirming that the applicant has no legal standing.